Thai Labor Crisis and the Implementation of the Approach to Promote the Potential of Labor Skills Under the Sirindhorn Vocational Training School to Create Jobs and Careers with the Concepts of Rebuilding Citizenship for a Sustainable Society (Journal of Carcinogenesis, 2025)
This study examines the role of the private sector in enhancing labor skills among juveniles at the Sirindhorn Vocational Training School to facilitate their reintegration into society. Employing a quantitative methodology, data were gathered from 70 participants to evaluate private sector engagement across five key dimensions: vocational skill development, physical health support, attitude transformation, training facility readiness, and inter-agency collaboration. The findings demonstrate that targeted vocational training contributes not only to employability but also to personal growth and social reintegration. Despite challenges such as rigid correctional policies and societal stigma, the study affirms that public-private cooperation plays a vital role in rebuilding citizenship among marginalized youth. These partnerships create structured pathways for transitioning from correctional care to meaningful employment, aligning with the broader objective of fostering a sustainable society. Although the multiple regression analysis showed no statistically significant predictors of perceived dignity enhancement, mental development and inter-sectoral cooperation exhibited relatively higher positive influence. These insights underscore the significance of skill-focused training and collaborative frameworks in supporting effective rehabilitation. The study recommends reinforcing public-private partnerships and advancing policy reforms to enhance reintegration outcomes and address Thailand’s ongoing labor shortages